Integrating Sustainable Development Goals into Model Bilateral Investment Treaties - Deskoski Toni; Dokovski Vangel (Iustinianus Primus Faculty of Law, 2025)
In today’s globalized economy, foreign direct investment (FDI) is a key component of national development strategies. The proliferation of multinational enterprises has led to an increase in foreign-controlled or influenced trading firms, often causing FDI to be overshadowed by portfolio investments. Nevertheless, FDIs contribute far more than financial resources, they often introduce cutting-edge technology, advanced management skills, innovation, and integration into international markets, which together drive more inclusive and sustainable economic growth in the host country.Three primary factors determine a country’s attractiveness to foreign investors. First, favorable macroeconomic conditions, such asrobust economic performancenaturally draw investor interest. Second, a stable political landscape reassures investors, encouraging long-term commitments. Third, legal predictability and a transparent regulatory framework are critical to building investor trust and ensuring consistency. In this regard, FDI becomes a fundamental engine of progress, delivering not just capital, but also vital knowledge, infrastructure, and employment opportunities.Techlogy transfer, within this setting, involves the sharing or adoption of scientific knowledge and production methods across organizations, sectors, or nations. This transfer occurs through channels such as foreign investments, international trade, patent agreements, technical training, and advisory services. This paper examines the role of sustainable developmentas facilitated by the latest generation of Bilateral Investment Treaties (BITs), and their potential to advance sustainable development in an increasingly interconnected global market. These modern BITs are crafted to encourage FDI from capital-abundant, high-tech economies, often OECD countries, into developing regions. By offering legal guarantees and reducing investment risks, these treaties aim to stimulate the movement of funds, technologies, and know-how from advanced economies to those still on the path of development.
Keywords: BITs, foreigninvestments, investors, sustainable developmentgoals, OECD